Root Cortex Provides a Venue for Gas-Space Formation and Is Essential for Plant Adaptation to Waterlogging - Yamauchi, Takaki; Abe, Fumitaka; Tsutsumi, Nobuhiro; Nakazono, Mikio (Frontiers in Plant Science, 2019)
Lysigenous aerenchyma, which develops by death and subsequent lysis of the cortical cells in roots, is essential for internal long-distance oxygen transport from shoot base to root tips of plants in waterlogged soil. Although many studies focus on the amounts of aerenchyma in roots, significance of the size of the root cortex in which aerenchyma forms has received less research attention. In the present study, we evaluated the cross-sectional area of each root tissue in adventitious roots of upland crops, wheat (Triticum aestivum) and maize (Zea mays ssp. mays), and the wetland crop, rice (Oryza sativa) under aerated or stagnant deoxygenated conditions; the latter can mimic the changes in gas composition in waterlogged soils. Our analyses revealed that the areas of whole root and cortex of the three species increased under stagnant conditions. In rice roots, cortex to stele ratio and aerenchyma to cortex ratio, which is associated with the areas of gas spaces, were much higher than those in wheat and maize roots, suggesting that these anatomical features are essential for a high capacity for oxygen transport along roots. To test this hypothesis, rates of radial oxygen loss, which is the diffusive flux of oxygen from within a root to the external medium, from thick and thin adventitious roots of rice were measured using a cylindrical (root-sleeving) oxygen electrode, for plants with shoots in air and roots in an oxygen-free medium. As expected, the rate of radial oxygen loss from thick roots, which have larger cortex and aerenchyma areas, was higher than that of thin roots. The rate of radial oxygen loss was highest at the apical part of rice roots, where aerenchyma was hardly detected, but at which cuboidal cell arrangement in the cortex provides tissue porosity. We conclude that high cortex to stele ratio in combination with large root diameter is a feature which promotes oxygen transport from shoot base to root tips of plants. Moreover, we propose that cortex to stele ratio should be a useful quantitative index for the evaluation and improvement of root traits contributing to tolerance of crops to soil waterlogging.